Differential effects of suppressors on hazardous sound pressure levels generated by AR-15 rifles: Considerations for recreational shooters, law enforcement, and the military. (12th February 2016) - Lobarinas, Edward; Scott, Ryan; Spankovich, Christopher; Le Prell, Colleen G.
Abstract: Objective : Firearm discharges produce hazardous levels of impulse noise that can lead to permanent hearing loss. In the present study, we evaluated the effects of suppression, ammunition, and barrel length on AR-15 rifles. Design : Sound levels were measured left/right of a user's head, and 1-m left of the muzzle, per MIL-STD-1474-D, under both unsuppressed and suppressed conditions. Study sample : Nine commercially available AR-15 rifles and 14 suppressors were used. Results : Suppressors significantly decreased peak dB SPL at the 1-m location and the left ear location. However, under most rifle/ammunition conditions, levels remained above 140 dB peak SPL near a user's right ear. In a subset of conditions, subsonic ammunition produced values near or below 140 dB peak SPL. Overall suppression ranged from 7–32 dB across conditions. Conclusions : These data indicate that (1) suppressors reduce discharge levels to 140 dB peak SPL or below in only a subset of AR-15 conditions, (2) shorter barrel length and use of muzzle brake devices can substantially increase exposure level for the user, and (3) there are significant left/right ear sound pressure differences under suppressed conditions as a function of the AR-15 direct impingement design that must be considered during sound measurements to fully evaluate overall efficacy.